Genomic Investigation and Biofilm Characterization of Methicillin-Resistant Staphylococcus aureus in Baghdad Province (Iraqi Journal of Medical Sciences, 2025)
Background:    Staphylococcus aureus (S. aureus) could readily form biofilm, which innervates the drug resistance abilities, resulting in life threatening infections involving different organs. The biofilm formation occurs due to a series of developmental proceeds including bacterial adhesion, aggregation, biofilm maturation, and dispersion, which are controlled by multiple genomic regulatory systems in S. aureus strains.Objective:    Determination of the biofilm capability with revealing the antimicrobial sensitivity outcomes and their relationship with the genomic content of S. aureus including Methicillin resistant S. aureus (MRSA) isolates across Baghdad province. Methods:    In this cross-sectional study, 200 variable pathogenic samples were collected from different patients ages across several medical centers in Baghdad, Iraq. Biofilm ability forming examining, antimicrobial susceptibility testing, and polymerase chain reaction (PCR) were applied to determine the adhesion capability, resistance pattern and gene distribution among identified S. aureus isolates, as well as biochemical tests to confirm isolates demonstration.Results: Out of 200 collected samples, only 130 coagulase positive cocci were approved, 72 MRSA being identified as verified groups of S. aureus isolates. As total, biofilm screening outcomes presents strong biofilm formation in 22 (18.92%) isolates, moderate in 24 (18.46%), weak in 26 (20.00%), and no-biofilm formation in 58 (44.62%) isolates. Across MRSA resistance-associated genes as mecA were detected respectively in 37 (80.4%). Genes within P value have been characterized into true-false ranges and presence-absent count. Antimicrobial screening showed most of isolates were sensitive to Gentamicin. Higher resistances were presented in Oxacillin and Rifampin. SCCmec pattern for MRSA was demonstrated according to PCR outcomes.Conclusion:Results of this study signalized that S. aureus including MRSA should be theorized as a serious opportunistic to pathogen to be aware in all people ages and units. Gentamicin and Tigecycline are fairly recommende d to treat some of S. aureus infections. Biofilm consider an important issue in medication and remediation capabilities and there virulence fairly related with genomic variation and its continuous developmentsKeywords: Staphylococcus aureus; MRSA; biofilm formation capacity; antibiotic resistance; genomic typingCitation: Qader TA, Ali MR, Alsakini AH. Genomic investigation and biofilm characterization of Methicillin-resistant Staphylococcus aureus in Baghdad province. Iraqi JMS. 2025; 23(1): 75-82. doi: 10.22578/IJMS.23.1.9